2016
DOI: 10.1111/jdi.12542
|View full text |Cite
|
Sign up to set email alerts
|

Elevated expression levels of serum insulin‐like growth factor‐1, tumor necrosis factor‐α and vascular endothelial growth factor 165 might exacerbate type 2 diabetic nephropathy

Abstract: Aims/IntroductionThe present study aimed to determine the associations between expressions of insulin‐like growth factor‐1 (IGF‐1), tumor necrosis factor‐α (TNF‐α) and vascular endothelial growth factor 165 (VEGF 165) in serum, and occurrence and development of type 2 diabetic nephropathy (DN).Materials and MethodsA total of 108 patients diagnosed as DN were randomly selected, including 50 patients in the microalbuminuria group, 44 patients in the macroalbuminuria group and 14 patients in the renal insufficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 36 publications
(45 reference statements)
7
29
0
Order By: Relevance
“…In accordance with recent studies [8, 18-20], through measuring plasma levels of VEGF, IL-1β, IL-6, TNF-α, and TLR4 we found that inflammatory factors and VEGF expression were higher in patients with DPN than in DN patients. These findings are in agreement with the theory that DPN may be associated with inflammation and endothelial dysfunction [21].…”
Section: Discussionsupporting
confidence: 70%
“…In accordance with recent studies [8, 18-20], through measuring plasma levels of VEGF, IL-1β, IL-6, TNF-α, and TLR4 we found that inflammatory factors and VEGF expression were higher in patients with DPN than in DN patients. These findings are in agreement with the theory that DPN may be associated with inflammation and endothelial dysfunction [21].…”
Section: Discussionsupporting
confidence: 70%
“…In addition, impaired PI3K-Akt signaling was reported in the myocardium of type 2 diabetic patients with chronic coronary heart disease, coupling with upregulated VEGFA 71 . Elevated VEGFA165 was also reported to exacerbate human type-2 diabetic nephropathy 77 , and administration of VEGFA neutralizing antibody resulted in amelioration of long-term renal changes in obese type-2 diabetic mice 78 . Thus, it will be interesting to know whether upregulated VEGFA associates with deficient phosphoinositide recycling in diabetic condition in heart or kidney, and tissue/organ specific signaling crosstalking and metabolic status must be considered to elucidate the underlying mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that levels of TNF-α are increased in all DN patients irrespective of gender and therefore TNF-α can be considered as a biomarker of DN [17,18]. Furthermore, several case-control studies conducted by Li et al and Babel et al [19,20] reported that elevated expression levels of serum TNF-α might exacerbate type 2 DN. Some studies have investigated the association between the TNF-α-308G/A polymorphism (rs1800629) and diabetic retinopathy in different populations [21,22].…”
Section: Introductionmentioning
confidence: 99%